Correction: Complete Revascularization and Survival in STEMI. Issue 1 (3rd November 2021) - Sustersic, Miha; Mrak, Miha; Svegl, Polona; Kodre, Anamarija Rebolj; Kranjec, Igor; Fras, Zlatko; Bunc, Matjaz
This article details a correction to: Sustersic M, Mrak M, Svegl P, Kodre AR, Kranjec I, Fras Z, et al. Complete Revascularization and Survival in STEMI. Global Heart . 2021; 16(1): 64. DOI:http://doi.org/10.5334/gh.1040